Martialling Peace: How the Peacekeeping Myth Legitimises Warfare by Nicole Wegner - Abdul Wasay Khan Mandokhail (NUST Journal of International Peace and Stability)
Nicole Wegner’s Martialling Peace: How the Peacekeeping Myth Legitimises Warfare (2023) critically examines the militarized underpinnings of peacekeeping through the lens of Feminist International Relations, Gender Studies, and Critical Military Studies. Using discourse analysis, Wegner dissects the “peacekeeping myth,” which portrays peacekeeping as neutral and benevolent while legitimizing military interventions. Focusing primarily on Canada, the book explores how peacekeeping aligns with national identity and state-building, reinforcing a martial ideology that extends to military and police institutions. The case of Canada’s involvement in Afghanistan and its treatment of Indigenous populations highlights the racial and colonial dimensions of peacekeeping narratives. The book challenges traditional perceptions of peace, arguing that peacekeeping often perpetuates violence under the guise of stability. While offering valuable critiques, its narrow focus on Canada limits its global applicability. Nonetheless, Martialling Peace provides essential insights into the interplay between militarism and peacekeeping, advocating for alternative, non-militarized peace approaches.